EVALUASI PROGRAM PENINGKATAN KUALIFIKASI AKADEMIK GURU MELALUI PELATIHAN GURU DALAM JABATAN - Juhri, Juhri; Suhardi, Muhammad (Jurnal Pendidikan Kreatif, 2022)
This study aims to evaluate the program for Improving the Academic Qualifications of Teachers in Positions. The research method is a qualitative descriptive program evaluation of the CIPPO model (Context, Input, Process, Product, Outcome). Collecting data through observation, interviews, questionnaires and documentation review. The results of the study: 1) The results of the evaluation of the context showed that the goals and objectives of the program were appropriate in accordance with Law Number 14 of 2005 concerning Teachers and Lecturers, 2) The results of the evaluation of the inputs showed that human resources and other resources were quite good, 3) the results Process evaluation shows that the Implementation of the Learning Process has gone well in accordance with the guidelines and signs that have been set, 4) Product Evaluation Results show that the GPA in general is good with very satisfactory predicate, 5) Outcome evaluation results, namely teacher competence in generally Good.